Prinsip Dasar Pertimbangan Pemilihan Media Pembelajaran - Sjahidul Haq Chotib (Awwaliyah: Jurnal Pendidikan Guru Madrasah Ibtidaiyah, 2018)
Learning media is an integral part of the learning process in the classroom. To achieve maximum learning outcomes, learners must have knowledge about the management of learning media both as teaching aids and as supporters so that the material / content of the lesson is clearer and can easily be mastered by students. In the learning process there are three interrelated components, namely: 1) learners (lecturers, teachers, instructors and tutors) who function as communicators, 2) students (students and students) who act as communicants, and 3) teaching materials which are messages that will be delivered to students to learn.